Identity and Meaning of Marriage in Samin Society, Blora Regency - Hidayaht , Ahmad Nur; Saipiatuddin, Saipiatuddin; Kurniawan, Novan; Herminasari, Nova Scorviana (Edukasi IPS, 2025)
Marriage has a deep meaning in the Samin community, a Javanese ethnic group in Blora Regency, Central Java. This study uses an ethnographic approach to understand the meaning and identity of marriage in Sami culture. Data was collected through in-depth interviews with community leaders, family members, and direct observation. The results of the study show that marriage in the Samin community is a social bond that involves two families, not just two individuals. Marriage ceremonies strengthen bonds between generations and maintain harmony within social groups. Marriage is also closely related to the concepts of religion and spirituality. Traditional wedding rituals and ceremonies, such as the marriage procedure for the Samin indigenous people, are carried out through the stages of nakokke, mbalesi gunem, ngendek, nyuwito, ngenger, paseksen, and tingkepan, which are passed down from generation to generation and become an integral part of the marriage procession. The role of traditional and religious leaders is central to formalising marriages. Overall, the meaning of marriage in the Samin community reflects the rich culture and spirituality that are deeply rooted in their lives. Marriage is one of the foundations for maintaining their cultural identity and determining the direction of social life in the future.